Economic burden of physical inactivity in hospitalizations due to dementia: a Brazilian nationwide study - Natan Feter; Jayne Santos Leite; Rodrigo Kohn Cardoso; Airton José Rombaldi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Our study aimed at determining the economic burden of leisure-time physical inactivity in hospitalizations due to dementia in Brazil. In this national-wide descriptive study, we used secondary data from the Brazilian Health Informatics Department and from the latest Brazilian National Health Survey (2013). Rate of hospitalization and economic cost were extracted from 2013. Leisure-time physical inactivity prevalence was used to estimate its population attributable fraction for dementia. Outcomes were stratified into sex (man/woman), age groups (< 50, 50-59, 60-69, 70-79, 80+), ethnicity (white, black, mixed race, other), and region (South, Southeast, North, Northeast, and Central). In 2013, 3,724 people were hospitalized due to dementia in Brazil resulting in a total cost of BRL 17,971,833.85 (USD 7,673,973.05). More than half of cost among men was spent with individuals younger than 59 years, white and mixed-race, and from Southeast region. Proportion of cost was higher in women older than 60 years and white. In 2013, 37% of all hospitalization from dementia in Brazil were attributable to physical inactivity, with values reaching 42.9% and 43.8% for men and women aged 80 or older, respectively. Physical inactivity cost BRL 6,994,254.75 (USD 2,986,546.78) in 2013 on hospitalizations due to dementia in Brazil. Higher attributable-cost was found for patients younger than 50 years and women older than 80. Strategies to preserve the quality of life of these patients are needed to reduce the burden for the patients, their family, and on the healthcare system.